Application of Fourier-Domain Post-Processing Technique for Ultrasonic Imaging with Matrix Phased Arrays in Advanced Manufacturing of Details and Machines; Materials Science Forum; Vol. 938 : Materials and Technologies in Mechanical Engineering - Dolmatov D. O. Dmitry Olegovich; Salchak Ya. A. Yana Alekseevna; Sednev D. A. Dmitry Andreevich; Pinchuk R. Roman (2018, 2018)
Title screen